Intense Physical Exercise Induces an Anti-inflammatory Change in IgG N-Glycosylation Profile - Tijardović, Marko; Marijančević, Domagoj; Bok, Daniel; Kifer, Domagoj; Lauc, Gordan; Gornik, Olga; Keser, Toma (Frontiers in Physiology, 2019)
Exercise is known to improve many aspects of human health, including modulation of the immune system and inflammatory status. Despite the general understanding that exercise reduces inflammation, the relation of the two is not yet fully understood. N-glycosylation of immunoglobulin G (IgG) and total plasma proteins was previously shown to reflect changes in inflammatory pathways, which could provide valuable information to further clarify exercise effects. In order to better understand the relationship between physical activity and inflammation, we examined the effect of intense exercise, in the form of repeated sprint training (RST), on IgG and total plasma proteins N-glycosylation in combination with traditionally used inflammation markers. Twenty-nine male physical education students were separated into treatment (RST, N = 15) and control (N = 14) groups. The RST group completed a 6-week exercise protocol while the control group was instructed to refrain from organized physical activity for the duration of the study. Three blood samples were taken at different time points: prior to start of the training program, the final week of the exercise intervention (EXC), and at the end of the four-week recovery period (REC). Following the end of the recovery period IgG N-glycosylation profiles showed anti-inflammatory changes in RST group compared to the control group, which manifested as a decrease in agalactosylated and an increase in digalactosylated and monosialylated N-glycans. Observed changes show the potential of intense physical exercise to reduce levels of systemic basal inflammation as well as the potential for IgG N-glycosylation to serve as a sensitive longitudinal systemic inflammation marker.